Conceptual Principles of the Planning of Modern Public Libraries - Jakovlevas-Mateckis, K.; Kostinaité, L.; Pupeliené, J. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
Over the last decades scientific progress has inspired not only major technological but most of the social and cultural changes as well. The information society of new quality has been developed. It could be characterised by the rapid growth of the amount and variety of information, development of the conception of information as a commodity, formation of knowledge and information industry, development of the information and communication technology, the impact of information and its technologies on all spheres of life including the nature of learning and work as well as on the style of everyday life.